Comparison of glasgow coma scale with full outline of unresponsiveness score in measuring consciousness level of endotracheal tube intubated patient in the intensive care unit - Oktarina, Yosi; Simajuntak, Charles A. (International Journal of Research in Medical Sciences, 2018)
Background: Assessment of consciousness level is a basic ability that medical personnel, especially doctors and nurses shall master. It is due to assessment of consciousness as a basis of clinical decision making and determining the patient's prognosis. There are various types of scales to measure consciousness level of patient. One of the most famous and most widely applied is Glasgow Coma Scale (GCS). However, the use of GCS is less precise in measuring consciousness level of patients, especially in Endotracheal Tube Intubated patients (ETT). Another measure of consciousness assessment is FOUR Score. In contrast to GCS, the use of four score as a measurement tool for consciousness assessment is still not yet familiar especially in Indonesia. Four score has different component with GCS where the four score component has no assessment of verbal response but it has brainstem and respiratory pattern assessment components. Methods: This research was an observational research using prospective non-experimental approach. The sampling technique used was consecutive sampling with a sample size of 33 people. Observation of the sample was undertaken at the same time. The instruments used in this research were GCS and FOUR Score observation sheet. Data analysis was performed by measuring the sensitivity, specificity, positive predictive value, negative predictive value and ROC. Results: Four Score has sensitivity of 86.7 specificity of 83.3 predictive positive value of 81.3 and negative predictive value 88.2 and under curve area of 0.848. Meanwhile, GCS has sensitivity of 80.0, specificity of 77.8, predictive positive value of 75, and negative predictive value of 82.4 and under curve area of 0.819. Conclusions: Four scores have a better assessment in measuring the consciousness level of ETT intubated patients.